ANALISIS HUBUNGAN KEPATUHAN TABLET FE DENGAN ANEMIA BUMIL - Masfufah, Masfufah; Kusumawardani, Emi; Sendra, Eny; Indriani, Ririn (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Anemia is one of the main factors contributing to the high maternal mortality rate (MMR) worldwide. In 2022, the number of cases of anemia in pregnant women in the working area of UPTD Puskesmas Kuta Selatan was recorded at 54.8%. The purpose of the study was to determine the relationship of Fe tablet compliance with anemia of pregnant women. The research design used in this study was cross sectional. The research was conducted at UPTD Puskesmas Kuta Selatan. The research was conducted in September 2023. The study population was all third trimester pregnant women who came to the UPTD Puskesmas Kuta Selatan Work Area with a sample of 48 people. The sampling technique used total sampling. The research instrument used a research questionnaire. Data analysis was performed univariate and bivariate. The results showed there was a relationship between Fe tablet consumption compliance (p value: 0.001) with the incidence of anemia in pregnant women. It is recommended for the Puskesmas to improve health counseling services that can increase the knowledge of pregnant women so that they are more responsible for themselves to comply with the recommendations given by health workers and for pregnant women to be more active in seeking information about the benefits of iron tablets, the definition of anemia, the causes of anemia, its impact on the mother and fetus, and how to prevent it.Keywords: Anemia, Pregnant Women, Adherence.